Pengaruh Desain Sambungan Las Spot Welding Terhadap Kekuatan Sambungan Pada Material Mild Steel - Priangga, Dimas Jasa; , Muh. Alfatih Hendrawan, ST, MT (2016)
Spot Welding or a welding method that uses electric resistance (Resistance Welding) in which two plate surfaces to be joined is pressed together by the two electrodes. Mild steel / carbon steel is one of the metals that are often used for connecting different types of materials in the industrial world. This is because these metals are used in almost all industrial sectors. Low carbon steel is a type of steel having a carbon content (C) of less than 0.30%. The advantages of this metal, among others, has good weldability characteristics, easily forged, machined, and has a relatively cheap price. This study uses material mild steel with a thickness of 1 mm. Variations of the parameters used in this study is the welding current of 4000 A, 5000 A and a welding time of 0.4 seconds, 0.5 seconds. Chemical composition testing using ASTM standard 1251, shear strength test specimens using standard ASME IX. The results showed that the study material is mild steel Iron (Fe) = 98.61%, carbon (C) = 0.272%, Silisum (Si) = 0337%, Magnesium (Mg) = 0402, and other elements below 0.1% , Variations of the design parameters, current and time affect the strength of the weld joint results. The greater current and time, will increase the yield strength of welded joints. variations in the design of an increase in power load bearing shear strength when design 2 stronger than design 3, resulting in the design of the welding point 2 rests up and down while the design of a 3 resting spot welding right and left. Thus variations in design will affect the strength of load bearing sliding on the connection. 2 design so that the weld point rests top and bottom will be better and more effective when compared with 3 design that relies spot welding right and left.